Empowering Superior Performance: Exploring the Mediating Role of Competitive Advantage in Driving Women's Agrosociopreneurial Motivation - Khouroh, Umu; Windhyastiti, Irany; Sri Ratnaningsih, Christina; Hana Setyanti, Sri Wahyu Lelly (Proceedings of International Conference of Graduate School on Sustainability, 2025)
This study aims to examine the role of competitive advantage in mediating the relationship between women's agro-socio-preneurial motivation and business performance. Data were collected from agrosocio MSMEs in Malang Regency with a sample of 83 MSMEs. This study uses a quantitative approach with an explanatory research type. Data analysis uses SEM-PLS to examine the impact of women's agro-socio-preneurial motivation on performance and the mediating role of competitive advantage in the relationship. The research findings show that of all motivational variables consisting of economic, social, passion-related-motivation, and political motivation, only social and political motivation have a major impact on women's agrosociopreneurship performance. Meanwhile, economic motivation and passion-related motivation do not have a major impact on improving performance. The findings also indicate that competitive advantage plays an important role in mediating the relationship between social and political motivation with a partial mediation for political mediation and a full mediation nature for social motivation. Women’s agrosociopreneurs who have strong business motivation, especially social and political motivation, can encourage innovation and create a competitive advantage that ultimately improves business performance.